Market Analysis of Škoda Auto in China - Šlégl, Martin (2011)
The main goal of this thesis -- "Market Analysis of Škoda Auto in China" is to analyze Škoda Auto Group in The People's Republic of China. Enjoying more than 100 years of history, Škoda Auto, based in Mladá Boleslav, Czech Republic, is one of the world's oldest automobile manufacturer and is a part of Volkswagen Group -- one of the world's largest auto concerns. Škoda Auto is a global brand presented in all major markets including emerging markets of Russia, India and most importantly China. Even though Škoda Auto has entered the Chinese automotive market very recently -- in 2007 with Octavia - in the first half of 2011 sold there 112 000 vehicles. Moreover, since 2010 Chinese market is the largest one for Škoda Auto followed by German and Czech markets. This thesis analyzes Škoda Auto in China as well as describes the main differences in model lines from European versions.